2006/09/10

The Harding Theorem


a=b
a^2=ab
a^2-b^2=ab-b^2
(a+b)(a-b)=b(a-b)
(a+b)(a-b)/(a-b)=b(a-b)/(a-b)
a+b=b

Therefore, if a=1, then 1=2

6 comments:

Matt said...

What's your schedule like this semester? Taking Logic, possibly?

Chuck Sutherland said...

Naw, just Pre-Calc and Environmental Geology. The formula is from my days of high school.
Fred Harding, my chemistry teacher showed us that.
It's wrong, but it looks nice.

Anonymous said...

I remit for your examination:

http://www.icengineering.com/n3ic/wrongs.gif

Chuck Sutherland said...

I've always been a fan of that Farside comic. :-)

Anonymous said...

Heh - for me that could be said of about 90% of all Far Side comics. :)

Chuck Sutherland said...

Hmm... Substitution...
2=2

2^2=2*2
4=4

2^2-2^2=2*2-2^2
4-4=4-4

(2+2)(2-2)=2(2-2)
(0)(0)=2(0)
0=0

(2+2)(2-2)/(2-2)=2(2-2)/(2-2)
(0)(0)/(0)=2(0)/(0)
Cannot divide by zero

2+2=2
Incorrect